PENGEMBANGAN E-LKPD DENGAN APLIKASI LIVEWORKSHEETS PADA ELEMEN PERHITUNGAN STATIKA BANGUNAN KELAS X DPIB DI SMK NEGERI 2 MEDAN - Sartika Aritonang, Rani; Sutrisno (STKIP Subang, 2026)
This research was motivated by the need for engaging and interactive learning media to support the learning process in the subject of Building Statics Calculation Elements. This research aims to determine the feasibility of the E-LKPD product with the liveworksheets application used in the Building Statics Calculation element. The research method used is Research and Development (R&D) with the ADDIE development model modified to ADD (Analysis, Design, Develop). The instrument used is a questionnaire. The questionnaire is used to test the feasibility of the E-LKPD through validation by material experts and media experts. The results of the study show that the developed E-LKPD product obtained an average value from material experts of 4.42 (category